Answer:
blue = 35
green = 29
red = 38
Step-by-step explanation:
Let r = red
Let g = green
let b = blue
r + g + b = 102
r = b + 3
b = g + 6 Subtract 6 from both sides of the equation
b - 6 = g
===================
substitute for red and green
(b + 3) + b + b - 6 = 102
b + 3 + b + b - 6 = 102
Combine like terms
3b - 3 = 102
Add 3 to both sides
3b - 3 + 3 = 102 + 3
3b = 105
Divide by 3
3b/3 = 105/3
b = 35
======================
r = b + 3
r = 35 + 3
r = 38
=======================
g = b - 6
g = 35 - 6
g = 29
========================
Answer:
- incorrect
- correct
- incorrect
Step-by-step explanation:
A + B = (-4x^2 +2x -5) +(3x^2 +6) = x^2(-4+3) +x(2) +(-5+6) = -x^2 +2x +1
The given sum is Incorrect.
__
A - C = (-4x^2 +2x -5) -(-5x -4) = -4x^2 +x(2+5) +(-5+4) = -4x^2 +7x -1
The given difference is Correct.
__
B + C = (3x^2 +6) +(-5x -4) = 3x^2 -6x +2
The given sum is Incorrect.
I think you have to divide
The first question is (7)
Answer:
6x - 15y = -63
15x -15y = -90
Step-by-step explanation:
We need to multiply the two equations by a constant that will eliminate the y terms.
The two equations are:
2x - 5y = -21
3x - 3y = -18
Let us multiply the first by 3 and the second by 6. The resulting equations will be:
6x - 15y = -63
15x -15y = -90
Note: To solve the system of equations we can simply subtract the first from the second.